Optimisation of soft handoff margin in WCDMA cellular system. (5th April 2010) - Tamilselvan, S.; Manivannan, K.
The focus of the paper is to analyse the downlink performance of a wideband code division multiple access (WCDMA) system with site selection diversity transmission (SSDT) power control during soft handoff (SHO) mode and to find the optimum SHO margin (MSH) in terms of maximum system capacity under energy-per-bit to noise spectral density ratio (Eb/N0) quality requirements. Analysing the dependency of the connection probabilities, percentage of users connected to one, two, or three base stations (BSs) simultaneously as a function of the MSH. We analysed the system capacity and required resources dependency on MSH for voice service and combined multimedia mobile services. System capacity dependency on MSH is analysed, by considering two types of user distributions, namely: 1) uniform user distribution; 2) a concentration of all the users in the location that requires maximum transmitted power (the worst case). The result of this analysis shows an increase in user capacity of about 16%-20% for the optimum MSH of 5-5.5 dB. Nevertheless, the resources required (number of scrambling codes) by the base station increases faster than the number of active users in terms of MSH.